The Purpose of Marriage among Single Malaysian Youth - Jamiah, Manap; Arena, Che Kassim; Suzana, Hoesni; Salina, Nen; Fazilah, Idris; Siti Fatihah, Ghazali (Elsevier Ltd., 2013)
Marriage is the starting point of family life cycle and the purpose of marriage affects the whole marital life. This study was conducted to explore the purpose of marriage among youth in Malaysia. Data was collected from 10 university students who consented to in-depth interviews. Besides, data was also gathered from the lists of purposes for marriage taken from 27 undergraduate students. All of them are single and aged between 23 to 34 years old. Three themes emerged from the study: religious motives, biological motives and socio-psychological motives. Religious motive is the main purpose of marriage as marriage performs a legal relationship that follows the guidelines of a religion. Fulfilling human nature to be in pairs, having a family and having a child to continue human legacy become the biological motives of marriage. Meanwhile, mutual love, friendship and happiness become the main socio-psychological motives of marriage. The purpose of marriage is influenced by the individual personal belief, life culture and life expectations. There is the need to conduct more research to investigate the effects of the purpose of marriage to the marriage well-being and family institutions.